2019
DOI: 10.1177/1350650119855904
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear analysis of mount angle effects on the dynamic stability of micropolar lubricated hydrodynamic lobed journal bearings

Abstract: Journal bearings are one of the most widely used types of supporting devices for industrial machinery, especially for high-speed rotary systems. Considering the importance of mechanical systems ability to control vibrations and motion disturbances, the design of noncircular journal bearings has been one of the appropriate techniques used in recent years. In the present work, the effects of mount angle as a noncircularity unique feature on the dynamic stability of lobed journal bearings with micropolar lubrican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The parameter l false¯ is related to the size of the particles and polymer chain molecules added to the base Newtonian oil lubricant. The nondimensional form of the above equations can be written as follows: Equation (2) is obtained using the following dimensionless expressions: The thickness of the lubricant film in the noncircular bearing space can be determined from the following equation when the rotor center is in static equilibrium point 28 : where false( X J 0 = ε 0 sin ϕ 0 normaland Y J 0 = ε 0 cos ϕ 0 false) are the coordinates of the static equilibrium position of the rotor center and θ 0 n shows the angle of lobe line of centers. The parameter δ = C ¯ m / C false¯ is called the preload factor.…”
Section: Modified Reynolds Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter l false¯ is related to the size of the particles and polymer chain molecules added to the base Newtonian oil lubricant. The nondimensional form of the above equations can be written as follows: Equation (2) is obtained using the following dimensionless expressions: The thickness of the lubricant film in the noncircular bearing space can be determined from the following equation when the rotor center is in static equilibrium point 28 : where false( X J 0 = ε 0 sin ϕ 0 normaland Y J 0 = ε 0 cos ϕ 0 false) are the coordinates of the static equilibrium position of the rotor center and θ 0 n shows the angle of lobe line of centers. The parameter δ = C ¯ m / C false¯ is called the preload factor.…”
Section: Modified Reynolds Equationmentioning
confidence: 99%
“…In addition, equations (2) and (32) represent the governing formulation of a nonlinear dynamic system and can be represented as follows: Parameter n f in equation (34) indicates the number of selected sample points on the meshed surface of the analyzed three-lobed noncircular journal bearing. 28 The velocity and acceleration of the rotor center and perturbed loading components as stated in equation (35) are assumed to be zero in the first step of the nonlinear dynamic analysis. Accordingly, the position of the rotor center at the first step of the solution deviates from the steady-state equilibrium point: In the next steps, by obtaining the new conditions of the rotor center using the numerical solution of the governing pressure and motion equations, the components of velocity and acceleration and the new position of the rotor center are determined.…”
Section: Dynamic Analysismentioning
confidence: 99%
“…In the dynamic analysis of micropolar lubricated offset bearing, Sharma and Krishna 37 concluded that higher offset provides better stability in terms of threshold speed. Very recently, the stability of micropolar lubricated elliptical dam bearing was presented by Sharma et al 38 Above studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] reflect that micropolar lubrication provides improved static and dynamic performance of circular and non-circular journal bearing configurations, as compared with Newtonian lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…Zare Mehrjardi et al (2020) concluded that mount angle affects the dynamic performance of lobed bearing to a great extent. Dewangan and Sarangi (2020) worked on the mixing of micro additive particles in lubricant and revealed that it further improves the load capacity of elliptical contact bearing and provides better lubrication performance.…”
Section: Introductionmentioning
confidence: 99%